A new active power‐decoupling topology and control mechanism to extend the lifespan and reduce the number of passive components. Issue 5 (7th January 2019) - Hwang, Soonhwan; Ogasawara, Satoshi; Orikawa, Koji; Takemoto, Masatsugu
Abstract : In this article, a new active power‐decoupling (APD) circuit without an additional discharging inductor is proposed for single‐phase power systems. In an APD circuit, a small film capacitor is used to extend the lifespan and remove ripple power derived from power systems. However, to manipulate power pulsation, additional circuits such as inductors, capacitors, and switches are required, which increase the manufacturing cost and parametric uncertainties. In the proposed circuit, rectification and a decoupling function are conducted on a coupled‐inductor at the same time to reduce the number of passive elements. Furthermore, a sliding mode control is used to ensure stable operation under parameter variation and disturbance. A design example is presented and the operation of the proposed topology is also verified with a simulation study and experimental results. The results show that the proposed APD method was able to remove passive components and reduce the withstand voltage of a buffer capacitor and insulated gate bipolar transistors (IGBT) while ensuring that both the input current and output voltage of the converter were well regulated under load variation. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.